ANALISIS NUMERIK PERILAKU DINDING PANEL BETON RINGAN DENGAN VARIASI DIMENSI AKIBAT BEBAN SIKLIK - Ferdinand Jaya Putra; Hanafiah; Siti Aisyah Nurjannah (JMTS: Jurnal Mitra Teknik Sipil, 2022)
The Construction of landed houses and offices reduces the availability of land, especially in big cities in Indonesia such as Jakarta. So that development is shifted vertically in order to make the best use of the land. Indonesia is a country surrounded by volcanoes that can cause earthquakes. Medium-magnitude earthquakes often cause damage to non-structural works, such as interior or exterior walls. Therefore, in this study, we will analyze the behavior of the wall panel with the help of finite element software, namely ANSYS. The method used in ANSYS has been verified by comparing the results of the research of Yu, et al., 2019 and the analysis of ANSYS, with a percentage difference of ?10%. The wall panels in this study had 4 models with variations in width dimensions made of lightweight concrete and given reinforcement to increase strength. Testing the behavior of the panel walls was carried out by testing static lateral and cyclic loads based on the recommended loading program from Yu, et al., 2019. The performance assessment of the panel wall model is carried out based on the panel wall behavior criteria according to the ACI 374.1-05, stress contour, and displacement contour. The results of the testing of the 4 models meet the standard criteria of ACI 374.01-5. The largest stress and displacement contour values are model D of 32.03 MPa and 75,52 mm.   Abstrak Gempa kerap menimbulkan kerusakan pada pekerjaan non-struktur, seperti dinding bagian dalam atau luar. Maka dari itu pada penelitian ini akan menganalisis perilaku dinding panel dengan bantuan software finite element yaitu ANSYS. Metode yang digunakan pada ANSYS akan diverifikasi dengan cara membandingkan hasil penelitian Yu, et al., 2019 dan analisis ANYS, dengan selisih persentase ≤ 10%. Dinding panel dalam penelitian ini memiliki 4 model variasi dimensi lebar yang terbuat dari beton ringan dan tulangan untuk menambah perkuatan. Pengujian perilaku dinding panel dilakukan dengan beban lateral dan siklik statik berdasarkan pembebanan yang direkomendasikan dari Yu, et al., 2019. Penilaian kinerja model dinding panel dilakukan berdasarkan pada kriteria perilaku dinding panel menurut ACI 374.1-05, kontur tegangan, dan kontur perpindahan. Hasil dari pengujian dari ke empat model memenuhi standar kriteria ACI 374.1-05. Nilai kontur tegangan dan perpindahan terbesar adalah model D sebesar 32,03 MPa dan 75,52 mm.